Transition metal-phosphorus-nitrogen-based catalyst as well as preparation method and application thereof
By preparing transition metal-phosphorus-nitrogen-based catalysts, and using hydrothermal, phosphating and nitriding treatments to form heterostructures, the problem of low anode reaction efficiency in traditional water electrolysis is solved, and the hydrogen evolution and glycerol oxidation reactions are efficiently carried out at low overpotentials, improving the overall efficiency and economic benefits of electrolyzing hydrogen production.
Patent Information
- Application Number
- CN202411764924.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
The oxygen evolution reaction kinetics of the anode in traditional water electrolytic systems are slow, resulting in the need of excessive overpotential and greater energy consumption, reducing the overall efficiency of the electrolysis process.
Transition metal-phosphorus-nitrogen-based catalysts are prepared using low-cost and resource-rich raw materials. Through hydrothermal treatment, phosphating treatment and nitriding treatment, a heterostructure between transition metal oxides, phosphides and nitrides is formed, thereby improving the specific surface area and catalytic performance of the catalyst.
In an alkaline environment, the transition metal-phosphorus-nitrogen-based catalyst can maintain long-term stability under high current density, reduce the overpotential of the hydrogen evolution reaction and glycerol oxidation reaction, improve energy conversion efficiency, and have good economic benefits.
Smart Images

Figure CN119571377A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electrocatalytic materials, and in particular relates to a transition metal-phosphorus-nitrogen based catalyst and a preparation method and application thereof. Background Art
[0002] Energy has always been the key driving force for the development of human society. However, the massive consumption of non-renewable and limited fossil fuels has led to the intensification of environmental pollution problems, prompting humans to explore renewable energy to achieve sustainable development. Hydrogen energy is a clean energy with the advantages of zero pollution, universal elements, and good combustion. It is considered to be an ideal substitute for traditional fossil fuels. There are many ways to produce hydrogen, such as methane reforming, water gas method, water electrolysis, etc. Among them, water electrolysis has the advantages of high purity, high efficiency, high cleanliness, and no carbon by-products, and has gradually become a promising hydrogen production technology.
[0003] Traditional water electrolysis technology uses the hydrogen evolution reaction (HER) as the cathode reaction and the oxygen evolution reaction (OER) as the anode reaction. However, in traditional water electrolysis systems, the oxygen evolution reaction at the anode end has slow kinetics, which requires excessively high overpotentials and greater energy consumption, thereby reducing the overall efficiency of the electrolysis process. Therefore, replacing OER with other thermodynamically more favorable anode reactions, especially those that can produce valuable products, to construct a hybrid water electrolysis system has become an innovative strategy to improve the overall energy conversion efficiency of hydrogen production by water electrolysis.
[0004] Glycerol, as a low-cost byproduct in the biodiesel production industry, can be oxidized into various value-added chemical products through electrochemical pathways. Electrocatalytic glycerol oxidation reaction (GOR) is a promising route for the production of fine chemicals. Therefore, coupling GOR with HER can obtain different energy efficiencies or additional value-added products.
[0005] Currently, the most commonly used catalysts for HER and GOR are precious metal catalysts or composite catalysts composed of precious metals and non-precious metals. The advantage of this type of catalyst is its high catalytic activity, but its high cost and scarcity greatly hinder its practical application. Summary of the invention
[0006] The object of the present invention is to provide a transition metal-phosphorus-nitrogen-based catalyst and a preparation method and application thereof. The present invention adopts low-cost and abundant raw materials to prepare a transition metal-phosphorus-nitrogen-based catalyst, the transition metal-phosphorus-nitrogen-based catalyst has good catalytic activity, can reduce the high overpotential in an alkaline environment, can maintain long-term stability under high current density, can meet the basic conditions for industrial hydrogen production, and can obtain high value-added by-products, with high economic benefits.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a transition metal-phosphorus-nitrogen based catalyst, comprising the following steps:
[0009] The conductive substrate is placed in a precursor solution and subjected to a hydrothermal treatment to form a transition metal oxide nanostructure array on the surface of the conductive substrate to obtain a transition metal oxide nanostructure array substrate; the precursor solution contains Co 2+ and [Mo7O 24 ] 6- ;
[0010] Phosphating the transition metal oxide nanostructure array substrate using phosphorus powder to obtain a transition metal phosphide nanostructure array substrate;
[0011] The transition metal phosphide nanostructure array substrate is subjected to nitridation treatment by using ammonia gas to obtain the transition metal-phosphorus-nitrogen based catalyst.
[0012] Preferably, the Co 2+ and [Mo7O 24 ] 6- The mass ratio of is 0.45-1.25:0.55-1.35; the temperature of the hydrothermal treatment is 50-380°C, and the insulation time is 2-15h.
[0013] Preferably, the phosphating treatment is carried out under the protection of an inert gas; the temperature of the phosphating treatment is 200 to 550° C., the time is 1 to 6 hours, and the heating rate to the phosphating treatment is 1 to 20° C. / min.
[0014] Preferably, the temperature of the nitriding treatment is 100-500° C., the time is 1-10 h, and the heating rate to the nitriding treatment is 1-20° C. / min; the ammonia atmosphere nitriding treatment is carried out in a mixed atmosphere of inert gas and ammonia.
[0015] Preferably, the conductive substrate is a foam metal substrate.
[0016] Preferably, the foam metal substrate includes a foam nickel substrate, a foam nickel-iron substrate, a foam cobalt substrate or a foam copper substrate.
[0017] The present invention provides a transition metal-phosphorus-nitrogen based catalyst obtained by the preparation method described in the above technical scheme, comprising a conductive substrate and a transition metal nanostructure array arranged on the conductive substrate, wherein the transition metal nanostructure array is composed of transition metal nanorods, and the components of the transition metal nanorods include oxides, phosphides and nitrides.
[0018] Preferably, the components of the transition metal nanorods include MoO2, Ni2P, Co2N and Co2P.
[0019] Preferably, the transition metal nanorods are prismatic in shape and have a size of 500 to 1500 nm.
[0020] The present invention provides the use of the transition metal-phosphorus-nitrogen based catalyst described in the above technical solution in hydrogen evolution reaction and / or glycerol oxidation reaction.
[0021] The present invention provides a method for preparing a transition metal-phosphorus-nitrogen based catalyst, comprising the following steps: placing a conductive substrate in a precursor solution, performing a hydrothermal treatment, so as to form a transition metal oxide nanostructure array on the surface of the conductive substrate, and obtaining a transition metal oxide nanostructure array substrate; the precursor solution contains Co 2+ and [Mo7O 24 ] 6- ; Phosphor powder is used to perform phosphating treatment on the transition metal oxide nanostructure array substrate to obtain a transition metal phosphide nanostructure array substrate; ammonia is used to perform nitriding treatment on the transition metal phosphide nanostructure array substrate to obtain the transition metal-phosphorus-nitrogen-based catalyst. The present invention forms a transition metal oxide nanostructure array on the surface of a conductive substrate by hydrothermal treatment; at the same time, the present invention forms a phosphide protective layer on the surface of the conductive substrate by phosphating treatment to improve the stability of GOR performance; nitriding treatment can further improve HER performance and its stability in an alkaline electrolyte environment. In the present invention, phosphating treatment and nitriding treatment can construct a heterogeneous structure between transition metal oxides, phosphides and nitrides, while increasing the specific surface area of the obtained transition metal-phosphorus-nitrogen-based catalyst, the catalytic performance and stability are also improved, which is beneficial to provide more active sites for hydrogen evolution reaction and glycerol oxidation reaction at the same time, and effectively reduce the energy barrier of electrocatalytic reaction. Moreover, in the preparation method of the present invention, the raw materials are cheap and the resources are abundant, the process is stable and reliable, the operation is simple, and it is easy to master, which overcomes the problems of high cost and scarcity of precious metal catalysts. The transition metal-phosphorus-nitrogen based catalyst obtained according to the preparation method provided by the present invention not only solves the problems existing in the noble metal catalyst, but also combines the advantages of oxides, phosphides and nitrides to form an interface synergistic enhancement effect, and has good electrocatalytic activity and stability.
[0022] The present invention also provides a transition metal-phosphorus-nitrogen-based catalyst, which includes a conductive substrate and a transition metal nanostructure array disposed on the conductive substrate, wherein the transition metal nanostructure array is composed of transition metal nanorods, and the components of the transition metal nanorods include oxides, phosphides and nitrides, specifically including MoO2, Ni2P, Co2N and Co2P. In the present invention, there is a heterojunction interface between the MoO2, Ni2P, Co2N and Co2P, and the heterojunction interface provides a large number of active sites for the adsorption and dissociation of hydrogen ions and water molecules; and the present invention combines the conductive substrate with the transition metal nanostructure array, effectively improving the conductivity of the resulting transition metal-phosphorus-nitrogen-based catalyst, reducing the electron transfer resistance, and accelerating the effective transfer of charges and ions, thereby greatly reducing the overpotential required in the reaction process. Based on this, the transition metal-phosphorus-nitrogen-based catalyst of the present invention exhibits very excellent hydrogen evolution performance and glycerol oxidation catalytic activity in an alkaline environment, and can be used at a large current density of 500mA / cm 2 (HER) and 200mA / cm 2 (GOR) maintains long-term stability and corrosion resistance, and is suitable for HER and GOR coupling reactions in alkaline environments; it can be seen from the examples that HER only requires an overpotential of 110 mV to reach 500 mA / cm 2 The current density of GOR is only 1.34V, which can reach 200mA / cm 2 Current density.
[0023] Furthermore, the transition metal-phosphorus-nitrogen-based catalyst prepared by the present invention can be used for producing hydrogen by electrolysis of water and can also produce high value-added chemicals, thus having high economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0025] Figure 1 is a scanning electron microscope image of the N-CoMoP catalyst obtained in Example 1;
[0026] Figure 2 is the X-ray diffraction spectrum of the N-CoMoP catalyst obtained in Example 1;
[0027] Figure 3The current-potential polarization curve of the hydrogen evolution reaction of the N-CoMoP catalyst obtained in Example 1 in a KOH aqueous solution;
[0028] Figure 4 This is a curve diagram of the electrochemical stability test of the N-CoMoP catalyst obtained in Example 1 in a KOH aqueous solution for hydrogen evolution reaction;
[0029] Figure 5 The current-potential polarization curve of the hydrogen evolution reaction of the N-CoMoP catalyst obtained in Example 2 in a KOH aqueous solution;
[0030] Figure 6 The current-potential polarization curve of the hydrogen evolution reaction of the N-CoMoP catalyst obtained in Example 3 in a KOH aqueous solution;
[0031] Figure 7 This is a performance comparison result diagram of the current-potential polarization curve of the N-CoMoP catalyst obtained in Example 1 and the CoMoO4-P obtained in Comparative Example 1 in a KOH aqueous solution for hydrogen evolution reaction;
[0032] Figure 8 The current-potential polarization curve performance comparison result of the N-CoMoP catalyst obtained in Example 1 and the CoMoO4-N obtained in Comparative Example 2 in the hydrogen evolution reaction in KOH aqueous solution;
[0033] Fig. 9 The current-potential polarization curve of the glycerol oxidation reaction of the N-CoMoP catalyst obtained in Example 1 in a KOH-glycerol-water mixed solution;
[0034] Fig.10 This is a graph showing the electrochemical stability of the N-CoMoP catalyst obtained in Example 1 in a KOH-glycerol-water mixed solution for glycerol oxidation reaction;
[0035] Fig.11 The current-potential polarization curve of the N-CoMoP catalyst obtained in Example 1 in a KOH-glycerol water mixed solution for the complete decomposition performance reaction;
[0036] Fig.12 HPLC detection chart of glycerol oxidation electrolysis test of N-CoMoP catalyst obtained in Example 1 in KOH-glycerol-water mixed solution at different potentials;
[0037] Fig.13 This is a comparison chart of the formic acid Faraday efficiency of the N-CoMoP catalyst obtained in Example 1 in a glycerol oxidation electrolysis test at different potentials in a KOH-glycerol-water mixed solution;
[0038] Fig.14This is a graph showing the performance comparison of the CoMoO4 nanostructure array substrate and the N-CoMoP catalyst for hydrogen evolution reaction obtained in Example 1;
[0039] Fig.15 This is a graph showing the performance comparison of the CoMoO4 nanostructure array substrate obtained in Example 1 and the N-CoMoP catalyst for glycerol oxidation reaction;
[0040] Fig.16 This is a comparison diagram of the current-potential polarization curves of the N-CoMoP catalyst obtained in Example 1 in the oxygen evolution / glycerol oxidation reaction in the KOH aqueous solution environment with or without the addition of glycerol. DETAILED DESCRIPTION
[0041] The present invention provides a method for preparing a transition metal-phosphorus-nitrogen based catalyst, comprising the following steps:
[0042] The conductive substrate is placed in a precursor solution and subjected to a hydrothermal treatment to form a transition metal oxide nanostructure array on the surface of the conductive substrate to obtain a transition metal oxide nanostructure array substrate; the precursor solution contains Co 2+ and [Mo7O 24 ] 6- ;
[0043] The transition metal oxide nanostructure array substrate and the phosphorus powder are placed in a tube furnace for phosphating treatment to obtain a transition metal phosphide nanostructure array substrate;
[0044] The transition metal phosphide nanostructure array substrate is subjected to nitridation treatment by using ammonia gas to obtain the transition metal-phosphorus-nitrogen based catalyst.
[0045] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art or are prepared by methods well known to those skilled in the art.
[0046] The present invention places a conductive substrate in a precursor solution and performs hydrothermal treatment to form a transition metal oxide nanostructure array on the surface of the conductive substrate to obtain a transition metal oxide nanostructure array substrate.
[0047] In the present invention, the conductive substrate may be a foam conductive substrate, which may include a foam nickel substrate, a foam nickel-iron substrate, a foam cobalt substrate or a foam copper substrate; in a specific embodiment of the present invention, the foam conductive substrate is a foam nickel substrate or a foam cobalt substrate.
[0048] The conductive substrate is placed in front of the precursor solution. The present invention can cut and wash the conductive substrate in sequence to obtain a pretreated substrate. In a specific embodiment of the present invention, the conductive substrate is cut into a rectangle with a length of 4.3 cm and a width of 2.2 cm. In the present invention, the washing includes acid washing, alcohol washing and water washing in sequence. The reagent used for the acid washing of the present invention is hydrochloric acid, the concentration of the hydrochloric acid can be 1-5 mol / L, the time of the acid washing can be 5-50 min, and the acid washing can be carried out under ultrasonic conditions. In a specific embodiment of the present invention, the concentration of the hydrochloric acid is 3 mol / L and the time of the acid washing is 10 min. The reagent used for the alcohol washing of the present invention is anhydrous ethanol, the time of the alcohol washing can be 5-50 min, and the alcohol washing can be carried out under ultrasonic conditions. In a specific embodiment of the present invention, the time of the alcohol washing is 10 min. The time of the water washing of the present invention can be 5-50 min, and the water washing can be carried out under ultrasonic conditions. In a specific embodiment of the present invention, the time of the water washing can be 10 min. In the present invention, the foam conductive substrate can provide a larger specific surface area. During the subsequent phosphating and nitriding treatments, a layer of phosphide or nitride will appear on the surface of the foam substrate, which is beneficial to improving the stability of the glycerol electrocatalytic oxidation reaction.
[0049] In the present invention, the precursor solution contains Co 2+ and [Mo7O 24 ] 6- ; The Co 2+ and [Mo7O 24 ] 6- The mass ratio of Co can be 0.45-1.25:0.55-1.35; in a specific embodiment of the present invention, the Co 2+ and [Mo7O 24 ] 6- The mass ratio of Co(NO3)2·6H2O and (NH4)6Mo7O is 0.757:0.959. 24 ·4H2O is mixed with water and then subjected to ultrasonic treatment to obtain the precursor solution. In the present invention, the ultrasonic treatment time can be 5 to 50 minutes; in a specific embodiment of the present invention, the ultrasonic treatment time is 10 minutes.
[0050] After obtaining the pretreated substrate and the precursor solution, the present invention loads the precursor solution into the lining of the hydrothermal treatment kettle, adds the pretreated conductive substrate, tightens the reactor and places it in a vacuum drying oven for hydrothermal treatment. The temperature of the hydrothermal treatment of the present invention can be 50 to 380°C, and the insulation time can be 2 to 15 hours; in a specific embodiment of the present invention, the temperature of the hydrothermal treatment is 150°C, and the insulation time is 6 hours.
[0051] After the hydrothermal treatment is completed, the present invention can cool the obtained sample to room temperature, soak the sample in water, and then dry the soaked sample to obtain a transition metal oxide nanostructure array substrate. In a specific embodiment of the present invention, the soaking time is 30 minutes; the drying is natural drying, and the drying time is 20 hours. In the present invention, the transition metal oxide nanostructure array substrate is a CoMoO4 nanostructure array substrate.
[0052] In the hydrothermal reaction of the present invention, the Mo element will cooperate with the Co ion to form a composite metal oxide (i.e., cobalt molybdenum oxide) CoMoO4. The present invention forms a transition metal oxide nanostructure array on the surface of a conductive substrate through hydrothermal treatment. The transition metal oxide nanostructure array is rod-shaped and can provide more active sites, which helps to improve the catalytic activity of the obtained catalyst; at the same time, the nanostructure array can greatly expose the electrochemical active sites of the obtained transition metal-phosphorus-nitrogen-based catalyst, which is conducive to accelerating the adsorption, dissociation and desorption of hydrogen ions and water molecules, and improving the energy conversion efficiency in the hydrolysis process.
[0053] After obtaining the transition metal oxide nanostructure array substrate, the present invention uses phosphorus powder to perform phosphating treatment on the transition metal oxide nanostructure array substrate to obtain a transition metal phosphide nanostructure array substrate.
[0054] In a specific embodiment of the present invention, the mass of the phosphorus powder is 50 mg. In the present invention, the phosphating treatment can be carried out under the protection of an inert gas, and the inert gas can be argon. In the present invention, the role of the inert gas is to serve as a protective gas. In a specific embodiment of the present invention, the phosphorus powder is placed in a quartz boat, the quartz boat containing the phosphorus powder is placed at the center of the upstream temperature zone of a double-temperature zone tubular furnace, and the transition metal oxide nanostructure array substrate is placed at the center of the downstream temperature zone of the double-temperature zone tubular furnace for phosphating treatment. In the present invention, the temperature of the phosphating treatment can be 200-550°C, the time can be 1-6h, and the heating rate of the phosphating treatment can be 1-20°C / min. In a specific embodiment of the present invention, the temperature of the phosphating treatment is 390°C, 420°C or 550°C; the time is 1h, 2h, 3h, 4h, 5h or 6h; the heating rate of the phosphating treatment is 1°C / min, 5°C / min, 10°C / min, 15°C / min or 20°C / min. After the phosphating treatment, the temperature of the tube furnace can be reduced to room temperature to obtain a transition metal phosphide nanostructure array substrate. In the present invention, the transition metal phosphide nanostructure array substrate is a CoMoP nanostructure array substrate.
[0055] In the present invention, the phosphating treatment can phosphate the transition metal oxide on the transition metal oxide nanostructure array substrate into a transition metal phosphide, that is, a transition metal phosphide nanostructure array substrate is formed, so that a transition metal phosphide (such as Co2P) protective layer is formed on the conductive substrate, which can improve the catalytic activity and stability of the resulting transition metal-phosphorus-nitrogen-based catalyst in the glycerol oxidation reaction. From a microscopic perspective, the present invention decomposes part of the transition metal oxide nanostructure array (i.e., CoMoO4 nanoarray) through phosphating treatment to generate CoO and MoO3, and the surface CoO and the conductive substrate react with the phosphorus element to form a transition metal phosphide, while MoO3 is retained; at this time, the transition metal phosphide will wrap a phosphide layer on the surface of the conductive substrate and the transition metal oxide. The XRD diagram in the embodiment shows that the transition metal phosphide mainly exists in the form of Ni2P and Co2P, wherein Ni2P is on the surface of the nickel foam substrate, Co2P is on the surface of the MoO3 / CoO nanorod array, and there is also some residual CoO, Co2P on the outer surface of CoO.
[0056] After obtaining the transition metal phosphide nanostructure array substrate, the present invention uses ammonia gas to perform nitridation treatment on the transition metal phosphide nanostructure array substrate to obtain the transition metal-phosphorus-nitrogen based catalyst.
[0057] In the present invention, the flow rate of the ammonia gas can be 10 to 100 sccm; in a specific embodiment of the present invention, the flow rate of the ammonia gas is 100 sccm. The present invention can carry out the nitridation treatment in a mixed atmosphere of an inert gas and ammonia gas, and the inert gas can be argon gas. In the present invention, the role of the inert gas is to serve as a protective gas and a carrier gas. In a specific embodiment of the present invention, the transition metal phosphide nanostructure array substrate is placed in the center of the temperature zone of a tubular furnace, and ammonia gas and argon gas are introduced to carry out the nitridation treatment. In the present invention, the temperature of the nitridation treatment can be 100 to 500°C, the time can be 1 to 10h, and the heating rate to the nitridation treatment can be 1 to 20°C / min. In a specific embodiment of the present invention, the temperature of the nitriding treatment is 350°C, 400°C, 450°C or 500°C; the time is 1h, 3h, 5h, 6h, 8h or 10h; the heating rate to the nitriding treatment is 1°C / min, 5°C / min, 10°C / min, 15°C / min or 20°C / min. After the nitriding treatment, the present invention can reduce the temperature of the tube furnace to room temperature to obtain a transition metal-phosphorus-nitrogen-based catalyst. In the present invention, the transition metal-phosphorus-nitrogen-based catalyst is an N-CoMoP catalyst.
[0058] In the present invention, the nitridation treatment can further improve the catalytic activity and stability of the hydrogen evolution reaction of the transition metal-phosphorus-nitrogen-based catalyst, effectively reduce the energy barrier required for the hydrogen evolution reaction, thereby reducing the cost of the water electrolysis process and the glycerol process. From a microscopic perspective, during the nitridation treatment, the originally phosphated MoO3 is reduced to MoO2, the remaining CoO is converted into nitride, and the Co2P and Ni2P in the system remain unchanged. Moreover, the nitride can significantly change the electronic structure and electron density of the obtained catalyst by introducing nitrogen elements, showing good chemical stability and excellent electrical conductivity, and the presence of the nitride can provide additional catalytic active sites, which are very beneficial for improving the HER catalytic performance and stability. More importantly, the formed nitride can form a heterojunction interface with the original phosphide / oxide, producing a synergistic effect, which effectively promotes the transfer of charge, optimizes the adsorption behavior of the reactant molecules on the catalyst surface, and significantly improves the performance and stability of the HER catalytic reaction. Therefore, the improvement of the hydrogen evolution reaction performance and stability is the result of the synergistic effect of nitride / phosphide / oxide.
[0059] The present invention also provides a transition metal-phosphorus-nitrogen based catalyst obtained by the preparation method described in the above technical scheme, which has a conductive substrate and a transition metal nanostructure array arranged on the conductive substrate, wherein the transition metal nanostructure array is composed of transition metal nanorods, and the components of the transition metal nanorods include oxides, phosphides and nitrides.
[0060] In the present invention, the composition of the transition metal nanorods may include MoO2, Ni2P, Co2N and Co2P. In the present invention, the shape of the transition metal nanorods is prismatic and the size is 500-1500nm. In the present invention, there is a heterojunction interface between the MoO2, Ni2P, Co2N and Co2P.
[0061] In the present invention, the transition metal-phosphorus-nitrogen based catalyst comprises a conductive substrate and a large number of transition metal nanorods composed of oxides, phosphides and nitrides stacked together on the surface of the conductive substrate. The presence of these nanorods provides abundant active sites for hydrogen evolution reaction and glycerol oxidation reaction.
[0062] The transition metal-phosphorus-nitrogen-based catalyst of the present invention has a heterogeneous structure of oxides, phosphides and nitrides, which improves the catalytic performance and stability while increasing the specific surface area of the obtained transition metal-phosphorus-nitrogen-based catalyst, and is conducive to providing more active sites for hydrogen evolution reaction and glycerol oxidation reaction at the same time, effectively reducing the energy barrier of electrocatalytic reaction. Specifically, different components in the heterogeneous structure each have different catalytic active sites, which can significantly increase the surface area of the catalyst. The larger surface area provides more active sites, which helps to improve the catalytic efficiency; moreover, different components in the heterogeneous structure can regulate the electronic structure through electronic interactions and charge rearrangement at the interface, thereby improving the availability of electrons. This electronic regulation helps to improve the electronic properties of the catalyst, thereby improving the kinetics of the reaction; furthermore, different components in the heterogeneous structure can produce a synergistic effect. For example: the presence of nitrides may regulate the electronic structure of the catalyst, so that the catalytic active sites of the phosphide can more effectively adsorb hydrogen ions, and the phosphide may enhance electron transfer by improving the conductivity of the catalyst. Such a synergistic effect makes the catalytic performance of the heterojunction interface surpass that of a single material; finally, the different components in the heterostructure can effectively improve the stability and corrosion resistance of the catalyst. This is because phosphides and nitrides have high chemical stability in alkaline environments, and their interfacial effects in catalytic reactions can effectively protect the structure of the catalyst from degradation or deactivation, thereby extending the service life of the catalyst.
[0063] The present invention also provides the use of the transition metal-phosphorus-nitrogen based catalyst described in the above technical solution in hydrogen evolution reaction and glycerol oxidation reaction.
[0064] The transition metal-phosphorus-nitrogen-based catalysts of the present invention exhibit excellent electrocatalytic activity and stability in alkaline electrolytes. For example, the transition metal-phosphorus-nitrogen-based catalysts synthesized by the present invention can greatly reduce the overpotential of the hydrolysis reaction. In an alkaline environment, the transition metal-phosphorus-nitrogen-based catalyst as a cathode catalyst for hydrogen evolution reaction only requires an overpotential of 110mV to reach 500mA / cm 2 The current density of transition metal-phosphorus-nitrogen-based catalysts as anode catalysts for glycerol oxidation reaction only requires a potential of 1.34V to reach 200mA / cm 2 When the transition metal-phosphorus-nitrogen-based catalyst is used as the cathode and anode catalyst in a hybrid full-solution device, it can generate 500mA / cm at a voltage of 1.52V. 2 Therefore, the performance of the transition metal-phosphorus-nitrogen based catalyst prepared by the present invention is better than that of most non-precious metal water electrolysis catalysts.
[0065] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0066] The conductive substrate used in the embodiment is a nickel foam substrate, 1.5 mm, with a pore size (ppi): 110 ± 10 and a density (g / m 2 ): 380±25, purchased from Kunshan Guangjiayuan New Materials Co., Ltd.
[0067] Example 1
[0068] The nickel foam substrate was cut into a rectangle with a length of 4.3 cm and a width of 2.2 cm, and the cut nickel foam substrate was placed in 3 mol / L hydrochloric acid for ultrasonic washing for 10 min. After that, the acid-washed nickel foam substrate was placed in anhydrous ethanol for ultrasonic washing for 10 min. After that, the alcohol-washed nickel foam substrate was placed in deionized water for ultrasonic washing for 10 min to obtain a pretreated substrate.
[0069] Co(NO3)2·6H2O (where Co 2+ 0.757 g) and (NH4)6Mo7O 24 4H2O (where [Mo7O 24 ] 6- 0.959g) was dissolved in 20mL deionized water and ultrasonicated for 10min to obtain a precursor solution. The precursor solution was loaded into the lining of the hydrothermal treatment kettle, the pretreated substrate was added, the reactor was tightened and placed in a vacuum drying oven, the temperature of the vacuum drying oven was raised to 150°C, and the reaction was carried out at a constant temperature of 150°C for 6h. After the reaction was completed, the vacuum drying oven was cooled to room temperature, the sample was taken out and soaked in deionized water for 30min to remove the excess reaction solution; after the soaking was completed, the obtained sample was placed in a fume hood and dried naturally for 20h to obtain a transition metal oxide nanostructure array substrate (recorded as CoMoO4 nanostructure array substrate).
[0070] A quartz boat containing 50 mg of phosphorus powder was placed in the center of the upstream temperature zone of the dual-temperature zone tube furnace, and the CoMoO4 nanostructure array substrate was placed in the center of the downstream temperature zone. Argon gas (flow rate of 10 sccm) was introduced into the tube furnace, and the temperature of the tube furnace was raised to 420°C at a rate of 10°C / min, and the reaction was carried out at a constant temperature of 420°C for 0.5h. After the reaction was completed, the temperature of the tube furnace was lowered to room temperature to obtain a transition metal phosphide nanostructure array substrate (referred to as a CoMoP nanostructure array substrate).
[0071] The CoMoP nanostructure array substrate was placed in the center of the temperature zone of a tube furnace, ammonia (flow rate of 100 sccm) and argon (flow rate of 10 sccm) were introduced, the temperature of the tube furnace was raised to 450°C at a rate of 3°C / min, and the reaction was carried out at a constant temperature of 450°C for 2 hours. After the reaction was completed, the temperature of the tube furnace was cooled to room temperature to obtain a transition metal-phosphorus-nitrogen-based catalyst (referred to as N-CoMoP catalyst).
[0072] The scanning electron microscope image of the N-CoMoP catalyst obtained in Example 1 is as follows Figure 1 As shown ( Figure 1 A in FIG. 1 is a scanning electron microscope image of the N-CoMoP catalyst when the scale bar is 2 μm, and B is a scanning electron microscope image of the N-CoMoP catalyst when the scale bar is 20 μm). Figure 1 It can be seen that a large number of stacked nanorods with a size of 500 to 1500 nm have grown on the foam conductive substrate, and these nanorods provide abundant active sites for hydrogen evolution reaction and glycerol oxidation reaction.
[0073] The X-ray diffraction spectrum of the N-CoMoP catalyst obtained in Example 1 is as follows: Figure 2 As shown. Figure 2 It can be seen that the main components of N-CoMoP catalyst are MoO2, Ni2P, Co2N and Co2P.
[0074] Test Example 1
[0075] The electrocatalytic hydrogen evolution performance of the N-CoMoP catalyst obtained in Example 1 was tested in a KOH aqueous solution environment.
[0076] This test scheme uses the American GAMRY Reference 3000 electrochemical workstation and a standard three-electrode system (working electrode, counter electrode and reference electrode) for testing, specifically as follows: the N-CoMoP catalyst obtained in Example 1 is used as the working electrode, the Hg / HgO electrode provided by Gamry is used as the reference electrode, the graphite rod is used as the counter electrode, and the 1 mol / L KOH aqueous solution is used as the electrolyte. The test results are shown in Figure 2. Figures 3-4 shown.
[0077] Figure 3 The current-potential polarization curve of the hydrogen evolution reaction of the N-CoMoP catalyst obtained in Example 1 in a KOH aqueous solution. Figure 3 It can be seen that the N-CoMoP catalyst obtained in Example 1 exhibits very excellent hydrogen evolution performance in an alkaline electrolyte environment, and only requires an overpotential of 110 mV to reach 500 mA / cm 2 (HER) current density.
[0078] Figure 4The electrochemical stability test curve of the N-CoMoP catalyst obtained in Example 1 in a KOH aqueous solution for hydrogen evolution reaction is shown in FIG. Figure 4 It can be seen that in an alkaline environment, the N-CoMoP catalyst has a high current density of 500 mA / cm 2 It has good stability and no obvious attenuation for more than 1200h.
[0079] Example 2
[0080] The N-CoMoP catalyst was prepared according to the conditions of Example 1, except that the temperature of the phosphating treatment was adjusted to 390° C., and the other conditions for preparing the catalyst remained unchanged.
[0081] Test Example 2
[0082] The hydrogen evolution performance of the N-CoMoP catalyst obtained in Example 2 was tested according to the conditions of Test Example 1. The results are as follows: Figure 5 shown.
[0083] Depend on Figure 5 It can be seen that the N-CoMoP catalyst obtained in Example 2 exhibits very excellent hydrogen evolution performance in an alkaline electrolyte environment, and only requires an overpotential of 161 mV to reach 500 mA / cm 2 The current density of the HER is 2.34 Å, and the current-potential polarization curves after 50 and 500 cycles of activation are basically the same, indicating that the N-CoMoP catalyst has excellent stability.
[0084] Example 3
[0085] The N-CoMoP catalyst was prepared according to the conditions of Example 1, except that the temperature of the nitridation treatment was adjusted to 400° C., and the other conditions for preparing the catalyst remained unchanged.
[0086] Test Example 3
[0087] The hydrogen evolution performance of the N-CoMoP catalyst obtained in Example 3 was tested according to the conditions of Test Example 1. The results are as follows: Figure 6 shown.
[0088] Depend on Figure 6 It can be seen that the N-CoMoP catalyst obtained in Example 3 exhibits very excellent hydrogen evolution performance in an alkaline electrolyte environment, and only requires an overpotential of 171 mV to reach 500 mA / cm 2 The current density of HER was 2.34 W·m-1·K-1 and 2.54 W·m-1·K-1. The current density of HER was 2.33 W·m-1·K-1. The current-potential polarization curve became better after 1000 cycles of activation, indicating that the hydrogen evolution catalytic activity of N-CoMoP catalyst became better after activation.
[0089] Comparative Example 1
[0090] The CoMoO4-P catalyst was prepared according to the conditions of Example 1, except that the catalyst after the phosphating treatment was not further subjected to the nitriding process.
[0091] Comparative test example 1
[0092] The hydrogen evolution performance of the CoMoO4-P catalyst obtained in Comparative Example 1 was tested according to the conditions of Test Example 1. The results are as follows: Figure 7 shown.
[0093] Depend on Figure 7 It can be seen that the hydrogen evolution performance of the CoMoO4-P catalyst obtained in Comparative Example 1 in an alkaline electrolyte environment is far inferior to that of the N-CoMoP catalyst, indicating that the formation of nitride is beneficial to improving the hydrogen evolution catalytic activity.
[0094] Comparative Example 2
[0095] A CoMoO4-N catalyst was prepared according to the conditions of Example 1, except that CoMoO4 was not subjected to phosphating treatment but directly subjected to nitriding treatment.
[0096] Comparative test example 2
[0097] The hydrogen evolution performance of the CoMoO4-N catalyst obtained in Comparative Example 2 was tested according to the conditions of Test Example 1. The results are as follows: Figure 8 shown.
[0098] Depend on Figure 8 It can be seen that the hydrogen evolution performance of the CoMoO4-N catalyst obtained in Comparative Example 2 in an alkaline electrolyte environment is far inferior to that of the N-CoMoP catalyst, indicating that the formation of phosphide is also beneficial to improving the hydrogen evolution catalytic activity.
[0099] Test Example 4
[0100] The glycerol oxidation performance of the N-CoMoP catalyst obtained in Example 1 was tested in a KOH-glycerol-water mixed solution environment.
[0101] This test scheme uses the American GAMRY Reference 3000 electrochemical workstation and a standard three-electrode system (working electrode, counter electrode and reference electrode) for testing, specifically as follows: the N-CoMoP catalyst obtained in Example 1 is used as the working electrode, the Hg / HgO electrode provided by Gamry is used as the reference electrode, the graphite rod is used as the counter electrode, and the KOH-glycerol-water mixed solution is used as the electrolyte (wherein the concentration of KOH is 1 mol / L and the concentration of glycerol (GLY) is 0.15 mol / L). The test results are shown in Figure 1. Figures 9-10 shown.
[0102] Fig. 9The current-potential polarization curve of the glycerol oxidation reaction of the N-CoMoP catalyst obtained in Example 1 in a KOH-glycerol-water mixed solution. Fig. 9 It can be seen that the N-CoMoP catalyst obtained in Example 1 exhibits a catalytic activity far exceeding that of OER in an electrolyte composed of an alkaline reagent and glycerol, and only requires an overpotential of 1.34 V to reach 200 mA / cm 2 (GOR) current density.
[0103] Fig.10 This is a graph showing the electrochemical stability of the N-CoMoP catalyst obtained in Example 1 in a KOH-glycerol-water mixed solution for glycerol oxidation. Fig.10 It can be seen that in the KOH-glycerol-water mixed solution, the N-CoMoP catalyst can 2 The stability was shown to be more than 520h.
[0104] Test Example 5
[0105] The performance of the hybrid full solution device of the N-CoMoP catalyst obtained in Example 1 was tested in a KOH-glycerol-water mixed solution environment.
[0106] The N-CoMoP catalyst obtained in Example 1 was used as the anode catalyst and cathode catalyst respectively, and a KOH-glycerol-water mixed solution was used as the electrolyte (wherein the concentration of KOH was 1 mol / L and the concentration of glycerol (GLY) was 0.15 mol / L) to form an N-CoMoP hybrid full-solution device. The performance test results of the hybrid full-solution device are shown in FIG. Fig.11 shown.
[0107] Depend on Fig.11 It can be seen that in the hybrid full solution device, a voltage of 1.52V can drive up to 500mA / cm 2 of current density.
[0108] Test Example 6
[0109] Detection of target products of glycerol oxidation of the N-CoMoP catalyst obtained in Example 1 in a KOH-glycerol-water mixed solution environment.
[0110] This test scheme uses the American GAMRY Reference 3000 electrochemical workstation and a standard three-electrode system (working electrode, counter electrode and reference electrode) to perform glycerol poplar oxidation electrolysis test, as follows: the N-CoMoP catalyst obtained in Example 1 is used as the working electrode, the Hg / HgO electrode imported from Gamry is used as the reference electrode, the graphite rod is used as the counter electrode, and the KOH-glycerol-water mixed solution is used as the electrolyte (wherein the concentration of KOH is 1 mol / L and the concentration of glycerol (GLY) is 0.15 mol / L). The glycerol oxidation products are qualitatively and quantitatively analyzed by high performance liquid chromatography (HPLC). For each analysis, 150 μL of electrolyte is diluted to 1.5 mL with 0.5 mol / L H2SO4 and then transferred to a sample bottle. The HPLC injection volume is 10 μL, and an Aminex HP-87H column (300×7.8 mm) is used for separation. The mobile phase consisted of 5mmol / L H2SO4, the column temperature was maintained at 40℃, the constant flow rate was 0.6mL / min, and the elution time was 20min. The composition of the electrolyte product was determined by the retention time of the elution peak. The test results are as follows Figures 12-13 shown.
[0111] Fig.12 The HPLC detection chart of the glycerol oxidation electrolysis test of the N-CoMoP catalyst obtained in Example 1 in a KOH-glycerol-water mixed solution at different potentials. Fig.12 It can be seen that the oxidation product of the N-CoMoP catalyst obtained in Example 1 in the electrolyte composed of an alkaline reagent and glycerol is mainly formic acid, followed by glycolic acid.
[0112] Fig.13 This is a comparison chart of the formic acid Faraday efficiency of the N-CoMoP catalyst obtained in Example 1 in the glycerol oxidation electrolysis test at different potentials in a KOH-glycerol-water mixed solution. Fig.13 It can be seen that the N-CoMoP catalyst obtained in Example 1 has a Faradaic efficiency of 76% or more for the main oxidation product formic acid in an electrolyte composed of an alkaline reagent and glycerol at different potentials. It is worth noting that at a potential of 1.45 V, the Faradaic efficiency of formic acid is as high as 96.9%.
[0113] Comparative test example 3
[0114] The electrocatalytic hydrogen evolution performance of the CoMoO4 nanostructure array substrate obtained in Example 1 was tested in a KOH aqueous solution environment.
[0115] The test was carried out in the manner and under the conditions of Test Example 1, except that the N-CoMoP catalyst was replaced with a CoMoO4 nanostructure array substrate, and the hydrogen evolution catalytic activity was tested and compared with the performance of the N-CoMoP catalyst. The results are as follows Fig.14 shown.
[0116] Depend on Fig.14 It can be seen that phosphating and nitriding treatments significantly improve the HER performance of the obtained catalytic material.
[0117] Comparative test example 4
[0118] The glycerol oxidation performance of the CoMoO4 nanostructure array substrate obtained in Example 1 was tested in a KOH-glycerol-water mixed solution environment.
[0119] The test was carried out in the manner and under the conditions of Test Example 4, except that the N-CoMoP catalyst was replaced with a CoMoO4 nanostructure array substrate, and the catalytic activity of glycerol oxidation was tested and compared with the performance of the N-CoMoP catalyst. The results are as follows Fig.15 shown.
[0120] Depend on Fig.15 It can be seen that the phosphating and nitriding treatments significantly improve the GOR performance of the obtained catalytic material.
[0121] Test Example 7
[0122] The oxygen evolution and glycerol oxidation performance of the N-CoMoP nanostructure array substrate obtained in Example 1 were tested in a KOH aqueous solution environment with or without glycerol added.
[0123] The oxygen evolution reaction was tested in the manner and conditions of Test Example 1, and the glycerol oxidation reaction was tested in the manner and conditions of Test Example 4, except that the N-CoMoP catalyst was tested in a KOH aqueous solution environment and a KOH-glycerol-water mixed solution environment, respectively, and the effect of the addition of glycerol on the performance of the catalyst was compared. The results are shown in FIG. Fig.16 shown.
[0124] Depend on Fig.16 It can be seen that the KOH aqueous solution without glycerol is undergoing oxygen evolution reaction, and the theoretical minimum potential required is as high as 1.23V. However, after adding glycerol to the KOH aqueous solution to form a KOH-glycerol-water mixed solution environment, the glycerol oxidation reaction occurs. The glycerol oxidation reaction can break through the theoretical minimum potential of the oxygen evolution reaction and achieve a very superior performance improvement. Specifically, 200mA / cm 2 The current density shows that the potential required for glycerol oxidation reaction is 350mV lower than that required for oxygen evolution reaction. This fully demonstrates the superiority of glycerol oxidation reaction as a replacement for traditional oxygen evolution reaction.
[0125] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a transition metal-phosphorus-nitrogen based catalyst, characterized in that: The following steps are involved: The conductive substrate is placed in a precursor solution and subjected to a hydrothermal treatment to form a transition metal oxide nanostructure array on the surface of the conductive substrate to obtain a transition metal oxide nanostructure array substrate; the precursor solution contains Co 2+ and [Mo7O 24 ] 6- ; Phosphating the transition metal oxide nanostructure array substrate using phosphorus powder to obtain a transition metal phosphide nanostructure array substrate; The transition metal phosphide nanostructure array substrate is subjected to nitridation treatment by using ammonia gas to obtain the transition metal-phosphorus-nitrogen based catalyst.
2. The preparation method according to claim 1, characterized in that: The Co 2+ and [Mo7O 24 ] 6- The mass ratio of is 0.45-1.25:0.55-1.35; the temperature of the hydrothermal treatment is 50-380°C, and the insulation time is 2-15h.
3. The preparation method according to claim 1, characterized in that: The phosphating treatment is carried out under the protection of an inert gas; the temperature of the phosphating treatment is 200 to 550° C., the time is 1 to 6 hours, and the heating rate to the phosphating treatment is 1 to 20° C. / min.
4. The preparation method according to claim 1, characterized in that: The temperature of the nitriding treatment is 100-500° C., the time is 1-10 hours, and the heating rate to the nitriding treatment is 1-20° C. / min; the ammonia atmosphere is a mixed atmosphere composed of an inert gas and ammonia.
5. The preparation method according to claim 1, characterized in that: The conductive substrate is a foam metal substrate.
6. The preparation method according to claim 5, characterized in that: The foam metal substrate includes a foam nickel substrate, a foam nickel-iron substrate, a foam cobalt substrate or a foam copper substrate.
7. The transition metal-phosphorus-nitrogen based catalyst obtained by the preparation method according to any one of claims 1 to 6, characterized in that: The invention comprises a conductive substrate and a transition metal nanostructure array arranged on the conductive substrate. The transition metal nanostructure array is composed of transition metal nanorods. The components of the transition metal nanorods include oxides, phosphides and nitrides.
8. The transition metal-phosphorus-nitrogen based catalyst according to claim 7, characterized in that The components of the transition metal nanorods include MoO2, Ni2P, Co2N and Co2P.
9. The transition metal-phosphorus-nitrogen based catalyst according to claim 7 or 8, characterized in that The transition metal nanorods are prism-shaped and have a size of 500-1500 nm.
10. Use of the transition metal-phosphorus-nitrogen based catalyst according to any one of claims 7 to 9 in hydrogen evolution reaction and / or glycerol oxidation reaction.